Accountability of PNS Performance through E-Kinerja at the Office of Agriculture and Livestock North Sulawesi Province Area - Mongan, Sofianty; Tewal, Bernhard; Lumanauw, Bode (European Journal of Life Safety and Stability (2660-9630), 2021)
Civil servants at the Regional Agriculture and Livestock Service Office of North Sulawesi Province have the task of carrying out regional government affairs based on the principle of autonomy and assistance in the field of regional agriculture and animal husbandry. The problem of the performance of the bureaucracy as a public servant and with the launch of technology to support the performance of the bureaucracy to be more effective and efficient in the form of an e-performance application is interesting to study. This study aims to determine the accountability of the performance of civil servants in implementing positions and to find out the factors that support and hinder the implementation of e-performance for civil servants in implementing positions at the Regional Agriculture and Livestock Service Office of North Sulawesi Province. This type of research is descriptive qualitative research. The research object selected was the Regional Agriculture and Livestock Service Office of North Sulawesi Province with 16 research informants. Data analysis techniques in the form of data reduction, data presentation and draw conclusions and verification. The results of the study show that through the application of e-kinerja, it can show the accountability of the performance of civil servants in implementing positions and the factors that support and hinder the implementation of e-performance for civil servants in implementing positions can be identified at the Regional Agriculture and Livestock Service Office of North Sulawesi Province.